Section 37C of the Pension Funds Act - disposition of death benefits by pension fund organizations - Jeram, Naleen Ganpatram Punjiah (Department of Commercial Law, 2023)
In 1976 section 37C was inserted into the Pension Funds Act1 ('the Act') commencing on 1 August 1976.2 This section regulates the payment of any benefit payable upon the death of a member of a pension fund organization ('pension fund') as defined in section 1 of the Act. Section 37C places a duty on the board of management ('the board') to distribute the death benefit. With effect from 19 April 1996, the boards of all pension funds have had to consist of at least four members, and members of the fund have the right to elect at least 50 per cent of the board.3 Section 37C imposes three duties on the board of a pension fund: first, to identify the dependants4 and the nominees of a deceased member; secondly, to effect a distribution amongst the said beneficiaries with reference to the various provisions of the section. Finally, the board must determine an appropriate mode of payment.